Peran Dinas Pertanian dalam Perlindungan Lahan Pertanian Pangan Berkelanjutan di Kota Bukittinggi - Andri Yeska Saputra; Lince Magriasti (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2022)
An important issue in today's development is sustainable agriculture. Along with the increasing rate of conversion of agricultural land to non-agriculture, the government made regulations to control land conversion by issuing Law No. RI. 41 of 2009 concerning the Protection of Sustainable Food Agricultural Land (LP2B). Just as Indonesia has experienced agricultural land conversion, in West Sumatra, especially in the City of Bukittinggi, agricultural land conversion has also occurred. In this case, the Local Government of Bukittinggi City, especially the Department of Agriculture and Food, is mandated to make a special policy on LP2B. However, this regulation has not yet been issued. This study aims to determine the role of the Department of Agriculture in the Protection of LP2B in Bukittinggi City. The method used in this study is descriptive method with data collection techniques through interviews and documentation.